Truth, reference, and realism - Novák, Zsolt; Simonyi, András. (Budapest, Hungary ; New York, N.Y. : Central European University Press, 2011)
The volume presents the material of the first Oxford-Budapest Conference on Truth, Reference and Realism held at CEU in 2005. The problem addressed by the conference, famously formulated by Paul Benacerraf in a paper on Mathematical Truth, was how to understand truth in the semantics of discourses about abstract domains whose objects and properties cannot be observed by sense perception. The papers of the volume focus on this semantic issue in four major fields: logic, mathematics, ethics and the metaphysics of properties in general. Beyond marking an important event, the collected papers are also substantial contributions to the above topic, from the most distinguished authors in these areas.
Introduction / András Simonyi, Zsolt Novák -- The reality of mathematics and the case of set theory / Daniel Isaacson -- Conceptualism and knowledge of logic: a budget of problems / Nenad Miščević -- What is logic? / Ian Rumfitt -- Absolute identity and absolute generality / Timothy Williamson -- The refutation of expressivism / Ralph Wedgwood -- Benacerraf's problem, abstract objects and intellect / Howard Robinson.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Truth -- Congresses; Reference (Philosophy) -- Congresses; Realism -- Congresses; Vérité -- Congrès.; Référence (Philosophie) -- Congrès.; Réalisme -- Congrès.; PHILOSOPHY -- Epistemology; PHILOSOPHY -- Movements -- Realism; Realism; Reference (Philosophy); Truth; Conference papers and proceedings